A Numerical Study on Hydrodynamic Energy Conversions of OWC-WEC with the Linear Decomposition Method under Irregular Waves - Jeong-Seok Kim; Kyong-Hwan Kim; Jiyong Park; Sewan Park; Seung Ho Shin (Energies, 2021)
A numerical study was performed to investigate the applicability of the linear decomposition method for the hydrodynamic energy conversion of an oscillating-water-column type wave energy converter (OWC-WEC). Hydrodynamic problems of the OWC chamber were decomposed into the excitation and radiation problems with the time-domain numerical method based on the linear potential theory. A finite element method was applied to solve the potential flow in the entire fluid domain including OWC chamber structure. The validity of the linear decomposition method was examined by comparing with the direct interaction method for the turbine–chamber interaction based on the linear pressure drop characteristics. In order to estimate the hydrodynamic energy conversion performance under the irregular waves, the response spectrum method was applied with the transfer function based on the linear decomposition method. Under the various irregular wave conditions, the pneumatic power of OWC-WEC calculated by the response spectrum based on the linear decomposition method agreed well with the direct irregular wave simulation results.